Safety Issues of Plasma-Derived Products for Treatment of Inherited Bleeding Disorders - Farrugia, Albert (Seminars in Thrombosis and Hemostasis, 2016)
The infection by blood-borne pathogens of a large proportion of the treated hemophilia population over the 1970s to 1990s represents a major tragedy that is embedded in the history of this condition. To avoid this historical repetition, the community of patients, treaters, and policy makers that contribute to hemophilia care need to learn from the events that gave rise to it. This requires an appreciation of the measures, which, through scientific developments, have enhanced greatly the safety of plasma-derived coagulation factor concentrates (pd CFCs). The objective conditions underlying and influencing the safety of all biological materials also require recognition. Although the stringent measures which ensure the safety of pd CFCs are very effective, pathogen transmission by other blood-derived therapeutics has continued due to a lack of effective technology and the continued emergence of new agents which transmit disease. This emphasizes the reality that the basic environmental factors influencing blood pathogen safety have not changed, albeit our capacity to counter them has improved greatly. These factors lead to threats to blood safety that are unpredictable and imposable on a global scale. The likelihood of a continued role for pd CFCs in hemophilia care, particularly in emerging countries challenged to maintain blood safety measures, ensures that these issues are more current than historical.
Keywords: blood safety; viruses; plasma products